2007
DOI: 10.1158/1078-0432.ccr-06-2245
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor Binding Proteins IGFBP3, IGFBP4, and IGFBP5 Predict Endocrine Responsiveness in Patients with Ovarian Cancer

Abstract: Purpose: This study sought to explore the predictive value of the insulin-like growth factor (IGF) binding proteins (IGFBP) as markers of response in ovarian cancer patients treated with the aromatase inhibitor letrozole. Experimental Design: IGFBP mRNA expression in cell lines was measured by quantitative reverse transcription-PCR and IGFBP protein expression measured in sections from primary tumors of patients treated with letrozole by semiquantitative immunohistochemistry. Results: Quantitative reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 33 publications
3
53
1
Order By: Relevance
“…Similar prognostic significance of IGFBPs was also recently recorded for early stage, surgically resected NSCLC [Shersher et al 2011]. The intricacies of the IGF-independent action of IGFBPs are beyond the scope of this review but have been described in several cancer models [Chang et al 2002;Dunlap et al 2007;Firth and Baxter, 2002;Hoeflich et al 2001;Li et al 2010;Migita et al 2010;Sureshbabu et al 2009;Walker et al 2007;Wolpin et al 2007].…”
Section: Introductionsupporting
confidence: 64%
“…Similar prognostic significance of IGFBPs was also recently recorded for early stage, surgically resected NSCLC [Shersher et al 2011]. The intricacies of the IGF-independent action of IGFBPs are beyond the scope of this review but have been described in several cancer models [Chang et al 2002;Dunlap et al 2007;Firth and Baxter, 2002;Hoeflich et al 2001;Li et al 2010;Migita et al 2010;Sureshbabu et al 2009;Walker et al 2007;Wolpin et al 2007].…”
Section: Introductionsupporting
confidence: 64%
“…Recent studies have shown that, in EOC tissues, decreased concentrations of IGFBP3 were significantly associated with advanced stage, suboptimal cytoreduction, and an elevated risk of progression (Katsaros et al 2001, Lu et al 2006, Torng et al 2008. In contrast, one study demonstrated the opposite findings (Walker et al 2007). Accumulating evidence supports the idea that IGFBP2 might act as a promoter, rather than a tumor suppressor, in EOC.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting family of proteins that emerged was the insulin-like growth factor binding proteins (IGFBPs) [72]. Three family members (IGFBP3, IGFBP4 and IGFBP5) were shown to be estrogenregulated in vitro with IGFBP3 and IGFBP5 being down-regulated by estrogen while IGFBP4 is upregulated [72].…”
Section: Predictive Biomarkersmentioning
confidence: 99%
“…Three family members (IGFBP3, IGFBP4 and IGFBP5) were shown to be estrogenregulated in vitro with IGFBP3 and IGFBP5 being down-regulated by estrogen while IGFBP4 is upregulated [72]. These effects were reversed by tamoxifen [72].…”
Section: Predictive Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation